Urinary chemerin as a potential biomarker for inflammatory bowel disease - Gunawan, Stefan; Elger, Tanja; Loibl, Johanna; Fererberger, Tanja; Sommersberger, Stefanie; Kandulski, Arne; Müller, Martina; Tews, Hauke Christian; Buechler, Christa (Frontiers in Medicine, 2022)
Purpose Systemic levels of the adipokine chemerin are elevated in different inflammatory conditions such as inflammatory bowel disease (IBD). In IBD, chemerin protein expression in colon mucosa is induced and serum chemerin levels are increased. Aim of this study was to identify chemerin protein in human feces and/or urine and to evaluate a possible association with IBD activity. Materials and methods Feces and urine of 40 patients with IBD and the respective sera of 34 patients were collected. Chemerin levels were analyzed by immunoblot in feces and urine samples. In addition, enzyme-linked immunosorbent assay (ELISA) was used to measure chemerin in all urine, feces and serum samples of the patients and in urine of 17 healthy controls. Results Chemerin was not detectable in 80% of the human feces samples by ELISA. Chemerin in human urine was detected by immunoblot and ELISA. Compared to serum levels, urinary concentration was about 6,000-fold lower. Urinary chemerin did not differ between patients with ulcerative colitis (n = 15) and Crohn’s disease (n = 25). Urinary chemerin was not related to its serum levels, did not correlate with serum C-reactive protein level and negatively correlated with serum creatinine. Of note, urinary chemerin of patients with a fecal calprotectin > 500 μg/g was significantly higher compared to patients with lower calprotectin levels and compared to healthy controls. Serum creatinine did not differ between the patient groups. Conclusion Urinary chemerin might present a novel non-invasive biomarker for monitoring IBD severity and clinical course.